Bitcoin The Virtual Currency Between Halal And Haram In Islamic Finance - Al-sahrawardee, Huda; Mahmood Ali, Amel; Yahya Ahmed, Wasan (Opción, 2019)
The technological and creative developments in the financial and banking fields are accelerating very rapidly, especially in the field of digital and vir- tual currencies which achieves significant profits. These technologies some- times are leads to the difficulty of accepting these developments especially in Islamic societies, because some of them do not conform to Islamic law. Which is requires the creation of a fatwa and the legitimacy of Shari’ah scholars and jurisprudence to be handled and traded. This paper highlight on the concept of Virtual Currency like Bitcoin and how does it work with the requirement of Islamic banking and finance also with Islamic law (Shari’ah) according to the opinion of Islamic scientists like (Malik & Ibn Taimiah). While it aims to find answers whether the virtual currency, especially Bitcoin is it permitted (Hala) or it’s forbidden (Haram) under Islamic Law (Shari’ah). It concludes that Bitcoin might be more suitable to deal with it in the Islamic world, especially Islamic banking than Usury Banks (Riba banks) as Trade Banks because of Bitcoin is free of interest rate.